Opinions and practices of veterinarians and dairy farmers towards herd health management in the UK - Hall, J.; Wapenaar, Wendela (BMJ Publishing Group, 2012)
The objective was to compare farm veterinary surgeons’ and dairy farmers’ opinions on herd health plans and herd health and production management with the aim of discovering and better understanding the differences. Two comparable questionnaires, one for farm veterinarians and one for dairy farmers, were distributed throughout the UK. While listing the ‘major roles’ of the veterinarian on the farm, veterinarians considered ‘optimising milk production’, ‘decreasing overall cost’ and ‘being an independent adviser’ as important roles, but these were not seem to be perceived as such by the farmers. In addition, when presenting themselves to clients, veterinarians seemed to favour the ‘friend of the farmer’ approach; a much smaller proportion of farmers seemed to prefer this approach. The majority of farm respondents (98 of 121; 81 per cent) valued the discussions with their veterinarian, and it was apparent from the relatively small proportion of veterinarians instigating a discussion on farm (33 of 125; 26 per cent) that there is the opportunity for a more proactive approach from veterinarians. The study underlines that ‘demonstrating cost-effectiveness’ is still a main concern for veterinarians and farmers and identifies areas that can be improved by more training and effective communication.